The corsair, the bishop, the governor and the runaways: Negotiating slavery in early eighteenth century Santa Marta, New Granada - Véronique Benei (Nuevo mundo - Mundos Nuevos, 2014)
Through the story of a corsair excommunicated by the bishop of Santa Marta after four blacks fled from his ship claiming free status, I show how the practice of corso in the eighteenth century revolved around, and contributed to the sustenance of an illegal and necessary local economy, with slaves a sought-after commodity. I then document the competing sites of power and authority –secular and religious- in this Spanish colony, especially regarding slave trade and slavery. Lastly, I analyse the strategy deployed by the fugitives, exploring how slaves negotiated their status in New Granada, compared with other Caribbean colonies.